2017
DOI: 10.1039/c7ra09036f
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of perfluorooctanoic acid-induced testicular oxidative stress and apoptosis by quercetin in mice

Abstract: Quercetin treatment attenuated PFOA-induced oxidative stress and apoptosis in the testes of mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Quercetin (purity ≥95%, high performance liquid chromatography) purchased from Sigma-Aldrich Co. (St Louis, MO, USA) was dissolved in DMSO and the dosages of quercetin chosen were based on previous reports 23,25,26. Commercial kits for urine albumin, urine creatinine, blood urea nitrogen, and serum creatinine were purchased from Jiancheng Biotechnology Company (Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
“…Quercetin (purity ≥95%, high performance liquid chromatography) purchased from Sigma-Aldrich Co. (St Louis, MO, USA) was dissolved in DMSO and the dosages of quercetin chosen were based on previous reports 23,25,26. Commercial kits for urine albumin, urine creatinine, blood urea nitrogen, and serum creatinine were purchased from Jiancheng Biotechnology Company (Nanjing, China).…”
Section: Methodsmentioning
confidence: 99%
“…In mouse testis, the lowest dose tested of 2.5 mg/kg/day PFOA increased MDA and hydrogen peroxide levels, decreased the expression of the oxidant-sensitive transcription factor, Nrf2, and inhibited the activities of antioxidant enzymes (superoxide dismutase and catalase) [91]. PFOA also induces oxidative stress in a dose-dependent manner from 0.5 to 5 mg/kg/day in the mouse liver and pancreas [25], and a variety of tissues including rat pancreatic β-cells [92], mouse testes and epididymis [93], and mouse ovary [94]. Similarly, in vivo and in vitro studies have demonstrated that PFOS exposure results in oxidative stress, evidenced by the production of ROS, changes in antioxidant enzymes, elevation of lipid peroxidation products and changes in Nrf2 [32,[95][96][97].…”
Section: Induces Oxidative Stressmentioning
confidence: 99%
“…Animal Bioassay In Vitro PFOA Association: [85] Association: [88]; [91]; [25]; [92] Association: [86]; [87]; [89]; [90]; [93]; [94]; [100]; [101]; [102] Long-chain PFAS a PFOS Association: [85] Association: [95]; reviewed in [32]; reviewed in [97]; [99] Association: [86]; [96]; reviewed in [32]; reviewed in [97]…”
Section: Epidemiologicalmentioning
confidence: 99%
“…Increased NRF2-ARE signaling in rat testes and liver of frogs exposed to PFOA, with greater expression of downstream NRF2 antioxidative targets (e.g., superoxide dismutase, catalase, heme oxygenase-1), has been documented. 31,32 Other oxidative stress protective pathways include the upregulation of metallothionein proteins (MTs) as well as recruitment of heat shock proteins (HSPs). 33,34 Activation of the metal response element promotes transcription of MTs and was observed in response to several PFAS.…”
Section: Oxidative Stressmentioning
confidence: 99%